2021
DOI: 10.3390/su13169244
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption and Spatial Assessment of Renewable Energy Penetration and Building Energy Efficiency in Malaysia: A Review

Abstract: The development of sustainable energy systems is very important to addressing the economic, environmental, and social pressures of the energy sector. Globally, buildings consume up to 40% of the world’s total energy. By 2030, it is expected to increase to 50%. Therefore, the world is facing a great challenge to overcome these problems related to global energy production. Malaysia is one of the top consumers of primary energy in Asia. In 2018, primary energy consumption for Malaysia was 3.79 quadrillion btu at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 144 publications
0
11
0
Order By: Relevance
“…Two more pieces of researches should be mentioned in this case. Haddad et al (2021) identified a framework for assessing urban energy sustainability [31], and Aldhshan et al (2021) discussed energy consumption and spatial assessment of renewable energy penetration and building energy efficiency [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Two more pieces of researches should be mentioned in this case. Haddad et al (2021) identified a framework for assessing urban energy sustainability [31], and Aldhshan et al (2021) discussed energy consumption and spatial assessment of renewable energy penetration and building energy efficiency [32].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instead of the industrial and transportation sectors, the property sector, especially high-rise buildings, is one of Indonesia's most significant energy users. The high-rise building energy is dominated by operating utilities, such as lighting, elevator, escalator, water pump, and air conditioning [5], [6]. Air conditioning and chillers significantly contribute to a building's energy consumption, particularly during peak demand [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the heightened interest in diminishing carbon emissions using renewable energy, extant research has overlooked the role of macroeconomic variables to support this relationship. The existing studies are focused on building energy alternatives and their measurements [19,20]. Furthermore, scholars are taking a debate on the theme of climate change on tourism which can be a motor of economic growth [9,21].…”
Section: Introductionmentioning
confidence: 99%